Investigations of Li-Picrate Salt Ion-pair to Ionic Dissociation in (PC+THF) at Various Combinations and Temperatures - Hazra, Ashoke (Chemical and Materials Sciences: Developments and Innovations Vol. 9, 2025)
Lithium perchlorate (LiClO4) is widely used as an electrolytic salt. Lithium perchlorate and other Li-salts have been used in the optimization of electrolyte solutions in organic aprotic solvents for primary and secondary rechargeable lithium batteries. Conductance of Li-Picrate was measured in different temperatures (25 oC, 35 oC, and 45 oC). The limiting equivalent conductance (\(λ\)0) and the ion association constant (KA) for Li-Picrate in propylene carbonate (PC) and tetrahydrofuran (THF) mixture (PC+THF) solvents at different percentages were evaluated using Debye-Huckel Onsager equation. It is observed that the limiting equivalent conductance increased linearly with the increase in temperature and the association constant values decreased with the rise in temperature. Thermodynamic parameters [i.e., Standard Gibbs Free Energy Change (iG0), Standard Enthalpy Change (iH0), and Standard Entropy Change (iS0) are estimated from the temperature dependence of the ion-association constant. The positive values of iS0 and positive values of iH0 indicate the ion-association process occurred spontaneously as well as endothermic at all respective temperatures. Supported by absorbance data from this primary study, it may be concluded that room temperature solubility of Li-Picrate in mixed (PC+THF) solvents at different percentages is higher than at higher temperatures. The entropy of ionization decreases slowly with an increase in temperature. From this angle, the ionization should decrease with temperature. Conductivity data helps us to conclude that if we go from room temperature to higher temperature conductance increases for Li-Picrate in (PC+THF) solvents at different percentages. This is due to the switchover of ion-pair to ionic dissociation of Li-Picrate salt.